Cost‐Effectiveness of Ivabradine for Heart Failure in the United States - Kansal, Anuraag R. (J Am Heart Assoc, 2016)
BACKGROUND: Ivabradine is a heart rate–lowering agent approved to reduce the risk of hospitalization for worsening heart failure. This study assessed the cost‐effectiveness of adding ivabradine to background therapy in the United States from the perspective of a commercial or Medicare Advantage payer. METHODS AND RESULTS: A cost‐effectiveness, cohort‐based Markov model using a state transition approach tracked a cohort of heart failure patients with heart rate ≥70 beats per minute in sinus rhythm who were treated with ivabradine+background therapy or background therapy alone. Model inputs, including adjusted hazard ratios, rates of hospitalization and mortality, adverse events, and utility‐regression equations, were derived from a large US claims database and SHIFT (Systolic Heart failure treatment with the I(f) inhibitor ivabradine Trial). In the commercial population, ivabradine+background therapy was associated with a cost savings of $8594 versus the cost of background therapy alone over a 10‐year time horizon, primarily because of reduced hospitalization. Ivabradine was associated with an incremental benefit of 0.24 quality‐adjusted life years over a 10‐year time horizon. In the Medicare Advantage population, the incremental cost‐effectiveness ratio for ivabradine was estimated to be $24 920/quality‐adjusted life years. CONCLUSIONS: The cost‐effectiveness model suggests that for a commercial population, the addition of ivabradine to background therapy was associated with cost savings and improved clinical outcomes. For a Medicare Advantage population, the analysis indicates that the clinical benefit of ivabradine can be achieved at a reasonable cost.